2023
DOI: 10.1519/ssc.0000000000000784
|View full text |Cite
|
Sign up to set email alerts
|

Testing and Profiling Athletes: Recommendations for Test Selection, Implementation, and Maximizing Information

Abstract: Understanding the physical qualities of athletes can lead to improved training prescription, monitoring, and ranking. Consequently, testing and profiling athletes is an important aspect of strength and conditioning. However, results can often be difficult to interpret because of the wide range of available tests and outcome variables, the diverse forms of technology used, and the varying levels of standardization implemented. Furthermore, physical qualities can easily be misrepresented without careful consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 94 publications
(123 reference statements)
2
25
0
Order By: Relevance
“…This may be due to time availability as few competitions are held during this period, therefore offering the opportunity to conduct thorough, uninterrupted assessments. Furthermore, fitness testing early in pre-season establishes baseline fitness levels, which lays the foundation for performance goal setting, fatigue monitoring, and return-to-play processes ( Maestroni et al, 2023 ; Weakley et al, 2023 ). A large proportion of fitness testing was also conducted during mid-season, possibly due to competition breaks, with data being used to assess mid-term progress and inform training adjustments and prescriptions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may be due to time availability as few competitions are held during this period, therefore offering the opportunity to conduct thorough, uninterrupted assessments. Furthermore, fitness testing early in pre-season establishes baseline fitness levels, which lays the foundation for performance goal setting, fatigue monitoring, and return-to-play processes ( Maestroni et al, 2023 ; Weakley et al, 2023 ). A large proportion of fitness testing was also conducted during mid-season, possibly due to competition breaks, with data being used to assess mid-term progress and inform training adjustments and prescriptions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, research has shown differences in physical attributes (e.g., speed, power, strength, change of direction ability, and aerobic capacity) between starting vs. non-starting players ( Hoppe et al, 2020 ), senior vs. youth ( Cardoso De Araújo et al, 2018 ), and elite vs. non-elite players ( Kobal et al, 2016 ). Therefore, fitness testing is necessary to provide practitioners (e.g., strength and conditioning [S&C] coaches, sports scientists) with objective information on the physical capacity of individuals and teams, which can be used to benchmark players, design and evaluate individualized training programs, reduce injury risk, inform return-to-play processes, and contribute to talent identification ( Turner et al, 2011 ; Taylor et al, 2022 ; Weakley et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The longitudinal quantification of elite women’s rugby league players anthropometric, physiological, and physical attributes are needed to establish normative standards for pre- and in-season periods. These standards can be used in athlete profiling, identifying strengths and weaknesses, performance monitoring, and talent identification strategies [ 13 ]. Therefore, the aim of this study is to use valid, and reliable testing measures to quantify changes in body composition, blood markers, energy requirements, strength, and aerobic capacity of women’s international rugby league players over three testing points in the lead up to the 2022 Rugby League World Cup (RLWC).…”
Section: Introductionmentioning
confidence: 99%
“…One core challenge for the (i) development of a decision-making skills diagnostic tool is the ecological validity addressing the question “[h]ow well a test relates to actual sporting performance and matches the athletes real sporting context” ( 8 , p. 4). Here, both the type of response capturing (e.g., motor vs. verbal responses) and the type of stimulus presentation are relevant ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%